Power Amplifier Kelas D Self Oscillating Dengan Power Mosfet Irfp4227, Irfp250n Dan Irfp460 - Alma'a, Rohmad Praditya; , Dr. Ir. Bana Handaga (2017)
Basically the amplifier is amplifying and enlarging the input signal. The input signal is copied and then rearranged into a reinforced signal, as it is well known that the audio amplifier types consist of Class A, Class B, Class AB and Class D amplifiers. In class D amplifiers have the advantage of great power efficiency (Can reach approximately 90%) when compared to other amplifier (class A, class B and class AB amplifier) so that the generated power efficiency is large. With the above problems, this study aims to compare Class D amplifier with 3 pairs of different Power Mosfets, IRFP4227, IRFP250N and IRFP460. The class D audio amplifier is a digital amplifier based power amplifier using the Pulse With Modulation (PWM) system where the input signal will be processed into a digital signal which will then be reinforced and reworked using a Low Pass Filter (LPF). The concept used in this audio amplifier D is self oscilating, that is by means of the internal loop feedback obtained from the R-C circuit so as to make the circle oscillate by itself. This study compared 3 pairs of Power Mosfet by using power supplay equal to 112,64 watt at Power Amplifier. After several test of Power Mosfet get data as follows: IRFP4227 power output of 96.01 watts with an efficiency of 85.24%, for IRFP250N of 94.06 watts with an efficiency of 83.50% and IRFP460 of 73.07 watts with efficiency 64.87% at the input signal of 1 KHz and at 8 Ω. In addition, the total harmonic distorsion (THD) in IRFP4227 is 0.78%, IRFP250N is 1% and IRFP460 is 1,65% and also the Signal to Noise Ratio (SNR) on IRFP4227 is 103,75 dB, IRFP250N is 102, 74 dB and at IRFP460 of 97.29 dB.